Transsexual men and access to health services: integrative review (Research, Society and Development, 2021)
A transsexual man is an individual who perceives himself as a man, identifies himself with the sociocultural attributes accepted as masculine, however, he was born with female genitalia and was initially socialized based on the norms imposed on women. It is known that these people suffer daily from prejudice coming from various spheres of society, one of them being the health field. Thus, it is necessary to understand the current scenario experienced by trans men in health, so that from that, it is possible to outline strategies capable of improving care. This study aims to identify and analyze the national scientific production on access to health services for transsexual men and the role of nursing during the care of this population. It is an integrative literature review. From the searches in the databases, 538 studies were found in total, 18 of which were pre-selected for evaluation and reading of the complete content and 12 selected for analysis. Based on the analysis of these articles, the main challenges encountered during access to health services by trans men became clear. As an example, there are: discriminatory attitudes, such as disrespect related to the use of the social name; the pathologization of transsexuality; professional unpreparedness related the demands and specificities of this group; the ignorance of some themes, which are only placed on the agenda, considering cisheteronormative aspects; among others.